การพัฒนาหลักสูตรเสริมประสบการณ์เพื่อสร้างความตระหนักในคุณค่าของชีวิตสำหรับนักศึกษาพยาบาล - ยศทวี วราภรณ์; ไชยศร เสริมศรี; วโรตมะวิชญ วีณา; แป้นแก้ว พงษ์ศักดิ์ (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยนี้มุ่งพัฒนาหลักสูตรและศึกษาผลการใช้หลักสูตรเสริมประสบการณ์เพื่อสร้างความตระหนักในคุณค่าของชีวิตสำหรับนักศึกษาพยาบาล กลุ่มตัวอย่างเป็นนักศึกษาพยาบาลศาสตร์ชั้นปีที่ 1 ภาคเรียนที่ 2 ปีการศึกษา 2559 วิทยาลัยพยาบาลบรมราชชนนี อุตรดิตถ์ จำนวน 36 คน ที่ได้จากการสุ่มอย่างง่าย ดำเนินการพัฒนาหลักสูตรตามกระบวนการ 4 ขั้นตอน คือขั้นตอนที่ 1 ศึกษาและวิเคราะห์สภาพความต้องการหลักสูตร ขั้นตอนที่ 2 การออกแบบและสร้างหลักสูตร ขั้นตอนที่ 3 การนำหลักสูตรไปใช้ ขั้นตอนที่ 4 การประเมินผลหลักสูตร เครื่องมือที่ผู้วิจัยสร้างขึ้นเพื่อใช้ในการวิจัย ได้แก่ 1) หลักสูตรเสริมประสบการณ์เพื่อสร้างความตระหนักในคุณค่าของชีวิตสำหรับนักศึกษาพยาบาล 2) แบบวัดความตระหนักในคุณค่าของชีวิต 3) แบบสังเกตและบันทึกพฤติกรรมความตระหนักในคุณค่าของชีวิต 4) แบบบันทึกสะท้อนคิดการเรียนรู้ประจำวัน วิเคราะห์ข้อมูลโดยใช้ค่าความถี่ค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน การทดสอบค่า t-test และการวิเคราะห์เนื้อหาผลการวิจัย พบว่า1. หลักสูตรเสริมประสบการณ์เพื่อสร้างความตระหนักในคุณค่าของชีวิตสำหรับนักศึกษาพยาบาลมีองค์ประกอบของหลักสูตร 6 องค์ประกอบ ได้แก่ 1) แนวคิดและหลักการของหลักสูตร 2) วัตถุประสงค์ของหลักสูตร 3) โครงสร้างเนื้อหาของหลักสูตร 4) การจัดกิจกรรมการเรียนรู้และสื่อการเรียนรู้ 5) การวัดและประเมิน ผลการเรียนรู้ 6) การประเมินผลหลักสูตร ออกแบบเป็น 5 หน่วยการเรียน ได้แก่ 1) การรู้จักตนเอง 2) การศรัทธาในความดี 3) การเห็นคุณค่าตนเอง 4) การเข้าใจชีวิตและรู้จักคิดเข้าใจผู้อื่น 5) การรับรู้และเข้าใจความทุกข์ แต่ละหน่วยประกอบด้วยแผนการเรียน 3 แผน จัดกิจกรรมการเรียนรู้ครั้งละ 1 แผนใช้เวลา 2 ชั่วโมง รวม 15 ครั้ง รวมทั้งสิ้น 30 ชั่วโมง กิจกรรมการเรียนการสอนเน้นความหลากหลายและการแสดงออกของผู้เรียนโดยทุกหน่วยมีกิจกรรมหลัก 4 กิจกรรม ได้แก่ 1) กิจกรรมสวดมนต์และทำสมาธิ 2) การฟังอย่างลึกซึ้ง 3) การสะท้อนความคิดและ 4) การเขียนบันทึกการเรียนรู้ประจำวัน ซึ่งอาจารย์และนักศึกษาที่เข้าร่วมจัดการเรียนรู้มีความเห็นว่าหลักสูตรมีความเหมาะสมที่จะใช้พัฒนานักศึกษาให้มีความตระหนักในคุณค่าของชีวิต เข้าใจตนเองและผู้อื่นได้ 2. นักศึกษาพยาบาลทุกคนแสดงพฤติกรรมตระหนักในคุณค่าของชีวิตระหว่างการเรียนแต่ละหน่วย และมีพฤติกรรมที่บางคนแสดงมากกว่า 2 ครั้ง ได้แก่ การอธิบายเหตุผลของการเลือกสิ่งที่เป็นสัญลักษณ์แทนตนเป็นความคิดและภาพวาด การยกตัวอย่างความเชื่อเกี่ยวกับพิธีกรรมต่างๆ การแสดงเหตุผลในความเชื่อเรื่องพลังเหนือธรรมชาติ การแสดงว่าตนเองมีความสุขเมื่อได้ช่วยเหลือผู้อื่น การเข้าใจพฤติกรรมของผู้เผชิญความทุกข์หนัก และสามารถช่วยเหลือผู้เผชิญความทุกข์ทางใจได้ พบว่าค่าเฉลี่ยคะแนนความตระหนักในคุณค่าของชีวิตของนักศึกษาพยาบาลโดยรวมหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 Development of Enrichment Curriculum to Cultivate Awareness in Values of Life for Nursing Students The purposes of this research were to develop the enrichment curriculum for cultivating nursing students’ awareness in values of life and to study the results of its implementation. 36first-year nursing students, studying in the second semester of the 2016 academic year at Boromarajonani College of Nursing,Uttaradit, were randomly sampled. This study was conducted in accordance with the four steps of the curriculum development process: Step1 Study and analysis of situations and needs; Step2 Curriculum design and construction; Step 3 Curriculum implementation; Step 4 Curriculum Evaluation. Researcher-constructed instruments included: 1) The enrichment curriculum for cultivating nursing students’ awareness in values of life, 2) A value-of-life awareness measurement scale 3) A behavior observation and recording form, 4) A recording form for daily reflection of learning. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, together with content analysis. The findings were as follows: 1. The constructed enrichment curriculum for cultivating nursing students’ awareness in values of life consisted of six components: 1)Key curriculum concepts and principles, 2) Curriculum objectives, 3) Curriculum content structure 4) Organization of learning activities and materials 5) Measurement and evaluation of learning 6 )Curriculum evaluation.Five learning units were planned: 1) Self awareness 2) Faith in goodness 3) Realization of self values 4)Understanding life and understanding others 5) Perception and understanding of sufferings. Each learning unit was composed of three learning plans. A two-hour period was spent for each plan which made the total of 30 hours within 15 learning periods. Instructional activities emphasized variety and students’ performance especially through the four principal activities arranged in all units i.e. meditation, deep listening, reflection, and daily recording of learning. Each unit also had its own particular learning activities. In the beginning stage, some students had troubles with some activities which need practicing such as the four principal ones in particular. With close guidance from instructors, however, students increasingly performed better. Both participated instructors and students reported that the constructed course was appropriate for developing students’ awareness in values of life and enabling them to understand themselves and others. 2. While learning in each unit, all students manifested awareness in values of life, some with a few times more than others; for instance, explaining the reasons for choosing their self symbols through ideas and drawings, giving examples of beliefs in rituals and faith , giving reasons for the beliefs in supernatural power, telling how happy they were when helping others, expressing understanding of severe sufferers’ behaviors , and helping them from mental distress. The comparison of the pre-test and post test mean scores revealed that the post-test mean score of students’ awareness in values of life in general was higher than the pre-test one at the statistically significance level of .01